Discrepancy in Electrolytic Conductivity Value Using Different Concentrations of KCl (aq.) as Calibrating Standard - Hanibah, Hussein; Hasyareeda Hassan, Nur; Ahmad, Azizan (Asian Journal of Chemistry, 2014)
Precise calibration of a conductivity probe in any conductance measurements is an important factor which determines the reliability of further analysis in an experiment. In normal practices standard solution of KCl (aq.) is used for an accurate calibration of the probe to determine the cell constant. Therefore, accurate measurements of electrical conductivity (k) for LiClO4 (aq.) at 25 °C are reported. A wide range of salt concentrations 10-3-10-8 mol cm-3 have been prepared through a series of dilutions from the stock solution used for the analysis. The conductivity measurement for LiClO4 (aq.) is carried out after the conductivity probe has been calibrated using different concentrations of primary standard KCl (aq.) at 25 °C under a controlled environment. Since, the experimental conditions are same in both systems, the same cell constant is adopted in further calculations. The data is analyzed after Kohlrausch's equation and the limiting molar conductivity (E0) values are determined at infinite dilution. It is experimentally shown that molar conductivity (E) value for LiClO4 (aq.) at 25 °C deviate from the regression function below the E value of the calibration standard used. This may suggest that the selection of the right concentrations of KCl (aq.) as a calibration standard is an important factor in liquid electrolyte system for a precise conductivity measurement. It is also noticed that the conductivity measurement of the analyte below the calibration value subjected to a large discrepancy in the conductivity measurement.